Respostas

A melhor resposta!
2014-03-27T12:34:10-03:00
S=t²-5t+6
0=t²-5t+6                Δ= b²-4ac                x= -b +-√Δ
                             Δ= (-5)²-4·1·6                  2·a             
                                                           x= -(-5)+-√1
a= 1                      Δ= 25-24                        2·1               x'= 5+1 = 6 = 3s 
b= -5                     Δ= 1                      x= 5+-1=                     2       2
c= 6                                                         2
                                                                                        x''=5-1 =4= 2s
                                                                                              2     2
2 5 2